Aislamiento de nanocelulosa a partir de Sargassum spp. de la costa caribeña - Silva Mendoza, Julio; Toxqui Téran, Alberto; Pérez Camacho, Odilia; Chávez Guerrero, Leonardo (Universidad Autónoma de Nuevo León, 2023)
Memorias